Formação e permanência dos jovens no meio rural: contribuições do Colégio Estadual do Campo Paulo Freire em Francisco Beltrão – PR - Cordeiro, Gilberto Mattos (2023)
The present research developed in the Graduate Program in Education - Masters, at the State University of Western Paraná (Unioeste), Francisco Beltrão campus, in the area of focus on Education, Line of Research: Society, Knowledge and Education, had as its object of study the training and permanence of young people in the countryside. The general objective was to analyze the contribution of Colégio Estadual do Campo Paulo Freire, located in the Missões Settlement in Francisco Beltrão - Paraná, for the formation and permanence of youth in the countryside. Through specific objectives, we sought to: a) understand Education and the Rural School historically inserted in the Brazilian agrarian issue and the struggle of popular social movements in the countryside; b) understand how secondary school and rural education are articulated to address the training needs of rural youth in the context of class society; c) to analyze the school formative processes present in the Colégio Estadual Paulo Freire, located in the Missões Settlement in Francisco Beltrão-Paraná and its contradictions in what corresponds to the identification and permanence of the youth in the countryside. We opted for a qualitative research methodology, following a case study, where young students and educators were submitted to questionnaires with open questions. For this, we used the theoretical framework that helps us understand the formation of young students in the school in the protected field, as well as the processes that involve all the dynamics that permeate the school. Thus, we highlight the authors: Alentejano (2012), Fernandes (2012), Stédile (2012), Araújo and D'Agostini (2012), Caldart (2012), Molina and Sá (2012), Bogo (2013), Snyders (2005 ); Frigotto (2009), Saviani (2011), Freitas (2018), Kuenzer (2017), Arroyo (2011), Martins (2020), Ghedini (2020), Santos (2022), Wanderley, (2007), among others. Thus, we can say that with the analysis of the pedagogical proposal adopted by the researched school, we have expanded the conception of the training process of young people who attend high school at Colégio Estadual do Campo Paulo Freire. We conclude that, given the obstacles and contradictions that impact the permanence of young students in rural areas, the school manages to develop a pedagogical practice that approaches the interests of the rural working class. This, based on continuing education, emphasizing the identification of educators with Rural Education and also with the reality in which the school is inserted. Even so, we observed that most young people are not convinced to stay in the countryside, as they are still attracted by urban life and cite access difficulties, lack of leisure, among others, as factors that also make it difficult for them to stay with their families.